MR and CT Arthrography of the Hip - Llopis, Eva; Fernandez, Ernesto; Cerezal, Luis (Seminars in Musculoskeletal Radiology, 2012)
CT arthrography (CTa) and MR arthrography (MRa) are useful tools for the investigation of intra-articular hip disease. They are minimally invasive techniques with a very low rate of complications and can be performed safely. CTa or MRa can be performed after an intra-articular injection of diluted contrast, but both techniques can also be performed after a single injection. As radiologists we should be able to address the surgeon's questions and work together to standardize terminology and classifications systems for accurate reporting. This update emphasizes radiological findings with a clinical perspective. CTa and MRa allow the precise diagnosis of labral tears, loose bodies, and intra-articular ligaments (capsular and ligamentum teres). The use of careful technique and a tailored protocol has improved our ability to detect and describe cartilage lesions. This is essential because knowledge of the status of the cartilage may dictate a specific surgical approach, and when cartilage lesions are extensive, they are a negative prognostic indicator for arthroscopic treatment.
Keywords: hip arthrography; CT arthrography; MR arthrography; labral tear; cartilage; femoroacetabular impingement